Contrasting responses of naturalized alien and native plants to native soil biota and drought - Ruppert, Hannah K.; Kleunen, Mark; Wilschut, Rutger A. (Functional ecology, 2024)
Terrestrial plant communities often become invaded by alien species, which may benefit from high growth rates, strong phenotypic plasticity and reduced negative impacts from local soil communities. At the same time, terrestrial communities are increasingly more often exposed to periods of drought. However, how drought affects the competition between alien and native plants directly, and indirectly, through changing impacts of soil communities on plant performance, remains poorly understood. Here, we performed a greenhouse pot experiment in which we examined biomass responses of five native and five naturalized alien species (all occurring in mesic grasslands) to drought and benign soil moisture conditions, while growing in interspecific, intraspecific or absence of competition, in the presence or absence of native soil biota. We expected that alien plant species are less negatively affected by soil biota, but more negatively affected by drought than native species, and that drought indirectly weakens soil‐community‐driven competitive benefits of alien plant species over native ones. On average, soil‐community effects on plant biomass were positive, but native performance was less positively affected by soil communities than alien performance, suggesting reduced impacts of soil‐borne enemies on alien plants. Drought more negatively affected alien‐ than native plant performance. Drought impacts on plant biomass did not depend on soil community presence, but in the presence of soil biota, plants overall invested more in root biomass when exposed to drought. The effects of competition were subtle and species‐specific. To better understand the observed positive soil‐community effects on plant performance in our study, we examined mycorrhizal root colonization of plants grown in absence of competition. Among‐species variation in mycorrhizal colonization explained plant performance differences between soils with and without live soil communities, indicating a key role for arbuscular mycorrhizal fungi as driver of plant performance. However, mycorrhizal colonization did not differ between alien and native plants and was unaffected by drought. Overall, our study suggests that drought may weaken alien plant invasions through stronger direct negative impacts on alien than on native plant performance, but that drought does not affect soil‐biota‐driven differences in plant performance between alien and native plants. Read the free Plain Language Summary for this article on the Journal blog. Read the free Plain Language Summary for this article on the Journal blog.